Cultivation of Phytase-Producing Bacteria as Probiotic Candidate on Molasses and Tempe-Processing Waste. Issue 1 (1st July 2022) - Gifari, Zaid Al; Agistna, Ihza; Anwar, Khairil; Rosyidi, Anwar; Ali, Muhamad; Amin, Muhamad
Abstract: Microbes that produce phytase enzymes are needed for livestock and fisheries. Animal feed treated with phytase will increase the availability of minerals, amino acids, and energy. For this reason, it is essential to growing phytase-producing bacteria on alternative media that are cheap and easy to obtain. This study aims to determine the ability of some bacteria that produce phytase to grow on alternative media such as molasses and tempeh waste. The indicators used were the growth rate of several phytase-producing bacteria within 3, 4, 5, and 6 hours of culture. The results showed that some bacteria were able to grow on alternative media of tempeh and molasses waste, although slower than growth on commercial media (LB). For this reason, tempeh and molasses waste can be used as alternative media to grow phytase-producing bacteria to produce cheap probiotics for livestock and fisheries.